Preoperative Considerations for the Ostomate - Wasserman, Molly A.; McGee, Michael F. (Clinics in Colon and Rectal Surgery, 2017)
Intestinal stomas significantly impact patients' quality of life. Stoma-related complications are common, but even without complications, patients are faced with new challenges in stoma management and daily activities. Preoperative patient education and stoma site marking, in conjunction with conscientious surgical stewardship, are key to patient satisfaction and successful operative outcomes.
Keywords: stoma; stoma complications; patient education; enterostomal therapist; stoma site marking